2022
DOI: 10.3390/ijerph19137627
|View full text |Cite
|
Sign up to set email alerts
|

Does Circular Economy Contribute to Smart Cities’ Sustainable Development?

Abstract: The purpose of this research paper is to investigate and identify the factors which can support the development of one characteristic of smart cities, namely, the smart environment. More specifically, the main goal is to measure the extent to which air pollution may be reduced, taking as determinants several circular economy, fiscal, and environmental factors. The Ordinary Least Squares, the Fixed Effects, and Random Effects regression models using balanced panel data were employed, over the 2011–2019 period, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…for translating theoretical research into practical actions. [14,17,19,21,23,24,26,30,31] Lack of universally applicable theoretical works for circular economy integration in diverse urban settings.…”
Section: Resultsmentioning
confidence: 99%
“…for translating theoretical research into practical actions. [14,17,19,21,23,24,26,30,31] Lack of universally applicable theoretical works for circular economy integration in diverse urban settings.…”
Section: Resultsmentioning
confidence: 99%
“…Many European Union member states currently lack the requisite waste-handling infrastructure. It is crucial to establish precise long-term policy goals to direct actions and expenditures, create systems and methods for waste treatment, and prohibit recyclable materials from being used at the bottom of the waste hierarchy [70]. A circular economy in cities will require unprecedented levels of cross-sector and public-private cooperation in the twenty-first century.…”
Section: Discussionmentioning
confidence: 99%
“…The definitions highlight several key aspects of the circular economy concept. In particular, the circular economy is a closed economic model (Sauve et al, 2016;Suarez-Eiroa et al, 2019;Morseletto, 2020), which focuses on reducing the amount of resources extracted and increasing the efficiency of the use of materials already in circulation (Geissdoerfer et al, 2017;Ranta et al, 2021;Dinca et al, 2022;Neves and Marques, 2022). CE is defined as an industrial system that is designed to be reproducible, regenerative, and resource efficient (Ellen MacArthur Foundation, 2002), which in turn aims to maximise the quality and usefulness of products, components, and materials throughout their life cycle, while minimising the generation of waste.…”
Section: Circular Economy Concept and Application Of Principles In Th...mentioning
confidence: 99%
“…Researchers (Fang and Zhang, 2010;Ma et al, 2016;Deselnicu et al, 2018;Petit-Boix et al, 2018;Uche-Soria and Rodríguez-Monroy, 2019;Margeta, 2019) in the hospitality and accommodation sector have shown that the most widely applied principle in the tourism sector is the 3Rs of "Reduce-Reuse-Recycle". The main objectives of applying circular economy principles relate to the promotion of environmentally friendly and low-carbon tourism products, taking into account energy saving and clean production, control of pollution sources and terminals, green goods and infrastructure systems from an industrial point of view; the use of renewable and more advanced resources; and the implementation of waste policies to improve the integrated management of municipal solid waste.…”
Section: Circular Economy Concept and Application Of Principles In Th...mentioning
confidence: 99%